The Expansion of Myeloid-Derived Suppressor Cells Correlates With the Severity of Pneumonia in Kidney Transplant Patients - Peng, Bo; Luo, Yulin; Zhuang, Quan; Li, Junhui; Zhang, Pengpeng; Yang, Min; Zhang, Yu; Kong, Gangcheng; Cheng, Ke; Ming, Yingzi (Frontiers in Medicine, 2022)
Background: Pneumonia is one of the most frequent but serious infectious complications post kidney transplantation. Severe pneumonia induces sustained immunosuppression, but few parameters concerning immune status are used to assess the severity of pneumonia. Myeloid-derived suppressor cells (MDSCs) are induced under infection and have strong immunosuppressive capacity, but the correlation between MDSCs and pneumonia in kidney transplant recipients (KTRs) is unknown. Methods: Peripheral blood MDSCs were longitudinally detected in 58 KTRs diagnosed with pneumonia using flow cytometry and in 29 stable KTRs as a control. The effectors of MDSCs were detected in the plasma. Spearman’s rank correlation analysis was performed to determine the correlation between MDSCs and the severity of pneumonia as well as lymphopenia. Results: The frequency of MDSCs and effectors, including arginase-1, S100A8/A9 and S100A12, were significantly increased in the pneumonia group compared with the stable group. CD11b+CD14+HLA-DRlow/-CD15- monocytic-MDSCs (M-MDSCs) were higher in the pneumonia group but showed no significant difference between the severe and nonsevere pneumonia subgroups. CD11b+CD14-CD15+ low-density granulocytic-MDSCs (G-MDSCs) were specifically increased in the severe pneumonia subgroup and correlated with the severity of pneumonia as well as lymphopenia. During the study period of 2 weeks, the frequencies of MDSCs and G-MDSCs were persistently increased in the severe pneumonia subgroup. Conclusions: MDSCs and G-MDSCs were persistently increased in KTRs with pneumonia. G-MDSCs were correlated with the severity of pneumonia and could thus be an indicator concerning immune status for assessing pneumonia severity.